THE EFFECT OF GREEN MARKETING STRATEGY ON CUSTOMER LOYALTY MEDIATED BY BRAND IMAGE (Case Study on The Body Shop Indonesia PT Monica Hijau Lestari Sentosa) - KEWAKUMA, ANGELINE STELLA VENTARI (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2021)
The purpose of this research to know the role of brand image to mediate the influence of green marketing on The Body Shop brand loyalty of beauty product. This research was conducted of 150 respondents in the city of Malang which used purposive sampling method. Methods of data collection using a questionnaire distributed through google forms.Data analysis technique used is Structural Equation Model (SEM) with approaches of Partial Least Square (PLS). Based on results of research conducted, found that green marketing has a positive and significant impaction brand image, green marketing has a positive and significant impact on consumer loyalty, brand image has a positive and significant impact on consumer loyalty and brand image significantly able to mediate the influence of green marketing on consumer loyalty beauty product of The Body Shop. This shows the greater the green marketing gained and perceived by consumers, the greater of sense of brand image and consumer loyalty that arise from them self to The Body Shop’s consumers.